Optimization of static wind power investment in the Australian national electricity market - Forsyth, Sebastian; Mahmoudi, Nadali; Saha, Tapan (2015 IEEE PES Asia-Pacific Power and Energy Engineering Conference (APPEEC), 2015)
This paper studies the Australian market conditions and subsidies in place to promote the growth of wind power through the use of a stochastic linear programming model. This model optimizes the profit obtained for a static investment based on a variety of wind and price scenarios. It is subject to different constraints which focus on the amount of initial capital injected by an investor, selling power through a Power Purchase Agreement (PPA) or using the Market Clearing Price (MCP). The Conditional Value-at-risk (CVaR) risk is also considered in this model to assist in differentiating between a risk-neutral and risk-averse investor. This has been evaluated for Portland on the coast of Victoria, Australia, using current data.